Anaerobic flora, Selenomonas ruminis sp. nov., and the bacteriocinogenic Ligilactobacillus salivarius strain MP3 from crossbred-lactating goats - Saranporn Poothong; Somboon Tanasupawat; Somchai Chanpongsang; Engkarat Kingkaew; Chackrit Nuengjamnong (My University, 2024)
Abstract This study aimed to examine the distribution of anaerobic bacteria in the rumen fluid of Thai crossbred goats and to screen potential probiotic strains capable of producing antimicrobial compounds and inhibiting bacteria that cause milk fat depression. Thirty-four strains of bacteria from the rumen fluid were divided into 13 groups within 12 genera based on 16S rRNA gene sequences. The RF1-5 and RF5-12 were identified as Streptococcus luteliensis and Bacillus licheniformis , respectively, and demonstrated non-ropy exopolysaccharide. Furthermore, mPRGC5 T was closely related to Selenomonas caprae JCM 33725 T (97.8% similarity) based on 16S rRNA gene sequences. It exhibited low average nucleotide identity, digital DNA–DNA hybridization, and average amino acid identity values with related type strains ranging from 84.9 to 86.0%, 21.3 to 21.8%, and 73.8 to 76.1%, respectively. The genotypic and phenotypic characteristics of mPRGC5 T strongly support this strain as a new species of the genus Selenomonas for which the name Selenomonas ruminis mPRGC5 T was proposed. The type strain is mPRGC5 T (= JCM 33724 T = KCTC 25177 T ). Ligilactobacillus salivarius MP3 showed antibacterial activity against Cutibacterium acnes subsp. acnes DSM 1897 T and Kocuria rhizophila MIII. The enterolysin A cluster gene was identified in its genome. The auto-aggregation of L. salivarius MP3 was 93.6 ± 0.2%. Additionally, co-aggregation of L. salivarius MP3 with C. acnes DSM 1897 T and K. rhizophila MIII had 92.2 ± 3.4% and 87.3 ± 4.5%, respectively. The adhesion capacity of strain MP3 was 76.11 ± 2.2%. Probiogenomic analysis revealed that L. salivarius MP3 was nonhazardous to animal supplementation and included acid- and bile-tolerant ability. However, strain MP3 contained three antibiotic resistance genes. Thus, the supplementation of L. salivarius MP3 could increase the milk fat content by suppressing C. acnes DSM 1897 T with antibiotic resistance gene horizontal transfer awareness.
Keywords: Lactobacillus salivarius; Strain (injury); Genomics and Phylogenetic Studies